1998
DOI: 10.2527/1998.763781x
|View full text |Cite
|
Sign up to set email alerts
|

The relative effectiveness of 2-hydroxy-4-(methylthio) butanoic acid and DL-methionine in young swine.

Abstract: We compared the effectiveness of 2-hydroxy-4-(methylthio) butanoic acid (HMB) and DL-methionine (DLM) as sources of L-methionine activity in methionine-deficient primary cultures of pig liver cells and methionine-deficient early-weaned pigs. Viable hepatocytes were obtained from minced pig liver and maintained in a high density, differentiated, nonproliferation cell culture system. Culture medium was supplemented with HMB, DLM, or L-methionine, and cells were pulse-dosed with L-[14C(U)]leucine for 24 h to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 7 publications
4
29
0
1
Order By: Relevance
“…Zimmermann et al, 2005;Kim et al, 2006;Shoveller et al, 2010), whereas others suggested a similar RBV between DL-Met and MHA (e.g. Reifsnyder et al, 1984;Chung and Baker, 1992;Knight et al, 1998;Roemer and Abel, 1999). …”
Section: Discussionmentioning
confidence: 96%
“…Zimmermann et al, 2005;Kim et al, 2006;Shoveller et al, 2010), whereas others suggested a similar RBV between DL-Met and MHA (e.g. Reifsnyder et al, 1984;Chung and Baker, 1992;Knight et al, 1998;Roemer and Abel, 1999). …”
Section: Discussionmentioning
confidence: 96%
“…There is wide disagreement over the bioavailability of MHA-FA compared to DLM. Some publications have proposed an equal bioavailability for MHA-FA compared to DLM (Reifsnyder et al, 1984;Knight et al, 1998;Rö mer and Abel, 1999;Gaines et al, 2005;Yi et al, 2006), whereas others have proposed a significantly lower bioavailability for MHA-FA, compared to DLM, on an equimolar or a product basis (Roth and Kirchgessner, 1986;Zimmermann et al, 2005;Kim et al, 2006;Dilger and Baker, 2008). In some of these experiments, Met was not showed to be limiting in all the diets or a diminishing incremental response to graded increases in Met intake was found.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the bioequivalence of HMTBa and DL-Met in pigs have ranged from 73 % on an equimolar basis (64 % on weight basis, 88 % HMTBa), when nitrogen retention was used as response criterion (Kim et al, 2006), to about 100 % (equimolar) in another study in which weight gain was assessed (Knight et al, 1998). In laying hens, HMTBa bioequivalence was found to be about 88 % on a molar basis (Liu et al, 2004).…”
Section: Comparative Bioefficacy Of the Methionine Enantiomers And Thmentioning
confidence: 99%